Determination of Material Handling Equipment for Lean In-Plant Logistics Using Fuzzy Analytical Network Process Considering Risk Attitudes of the Experts - YILMAZ, Omer Faruk; Oztaysi, Basar; DURMUSOGLU, Mehmet Bulent; ONER, Sultan Ceren (International Journal of Industrial Engineering: Theory, Applications and Practice, 2017)
Using right material handling equipment (MHE) is substantial in terms of manufacturing costs even if related manufacturing environment is lean. In this paper, right materials handling equipment selection problem is investigated at the line feeding systems such as kitting and milk-run systems. Each system has three alternatives for selection and main problem is the difficulty in selecting the appropriate one, since these equipments are integrated with each other by means of a total of nine possible combinations. In order to select most appropriate combination, alternative equipment is evaluated separately at first and then, resulting priorities are aggregated to find the best alternative. In the equipment selection decision model, there are four main criteria and seventeen sub-criteria. Since the dependencies are appeared within the criteria, Fuzzy Analytic Network Process (FANP) technique is preferred. Besides that, risk attitude of the experts are also incorporated into the model using linguistic terms in order to reach accurate results. The real world application is implemented in an electronic device assembly plant located in Istanbul. The result of the numerical application demonstrated that Tugger Automated Guided Vehicle (AGV) should be used for the milk-run system and a Belt conveyor should be acquired for the kitting system.